Sistem Informasi Perpustakaan Berbasis Website di SMK Bani Muchtar Rancaekek - Ricky Rohmanto; Muhamad Fahmi Nugraha; Tami Indri Yani (Ma'soem University, 2021)
SMK Bani Muctar Rancaekek is a private vocational high school located in the Rancaekek area. The Library Information System at SMK Bani Muchtar is still based on semi-computerization, so it is necessary to improve the system that can facilitate service in the library. Library Information System Design is a system that will be built to reduce significant problems in the previous library information system. Some of the problems that often occur are the loss of loan data, difficulty in knowing the availability of books, limited hours of library service. The development method in this library information system is built based on the OOAD (Object Oriented Analysis and Design) development method approach with the model used, namely RUP (Rational Unified Process) equipped with development tools, namely UML (Unified Modeling Language). The author can draw the conclusion that the system to be built can be useful, assist in the process of library services, and can overcome problems in the previous system.